Does Tax Evasion Affect Economic Crime?. (2nd June 2020) - Argentiero, Amedeo; Chiarini, Bruno; Marzano, Elisabetta
Abstract: This paper examines the effect of tax evasion on criminal activities in Italy. Specifically, we consider three types of crime that are related to economic determinants: property crimes (including robbery, theft and car theft), fraud and usury. We estimate different econometric models using annual data from the Italian provinces (NUTS‐3 level) for the 2004–12 period. We find that tax evasion positively affects economic crimes, and our results suggest that tax evasion is an incentive to engage in criminal activities, in addition to more standard determinants that we include in the analysis, such as labour market opportunities and deterrence. Moreover, these crimes demonstrate different levels of persistence over time and reflect different adjustment costs.